Biochar Preparation, Characterization, and Adsorptive Capacity and Its Effect on Bioavailability of Contaminants: An Overview - Obemah D. Nartey; Baowei Zhao (Advances in Materials Science and Engineering)
This paper provides an updated review on the subjects, the available alternative to produce biochar from biomass, quantification and characterization of biochar, the adsorptive capacity for the adsorption of contaminants, and the effect of biochar addition to agricultural soils on contaminant bioavailability. The property of biochar produced is much dependent upon the composition and type of biomass and the conditions at which biomass is carbonized. The physical and chemical characterizations are necessary to identify the basic structure and property of biochar and to predict its potential in various environmental application. Biochar is a promising alternative to remedy the soils contaminated with heavy metals and organic compounds through adsorption and immobilization due to its large surface area, charged surface, and functional groups. Overall, the bioavailability of heavy metals and organic compounds decreases when biochar is amended into soils.